Inflammatory potential of the diet and risk of gastric cancer in the European Prospective Investigation into Cancer and Nutrition (EPIC) study - Agudo, A; Cayssials, V; Bonet, C; Tjønneland, A; Overvad, K; Boutron-Ruault, M; Affret, A; Fagherazzi, G; Katzke, V; Schübel, R; Trichopoulou, A; Karakatsani, A; et al. (Oxford University Press, 2018)
Background Chronic inflammation plays a critical role in the pathogenesis of the two major types of gastric cancer. Several foods, nutrients, and non-nutrient food components seem to be involved in the regulation of chronic inflammation. Objective To assess the association between the inflammatory potential of the diet and the risk of gastric carcinoma, overall and for the two major subsites: cardia cancers and non-cardia cancers. Design A total 476160 subjects (30% males, 70% females) from the European Investigation into Cancer and Nutrition (EPIC) study were followed for 14 years, during which 913 incident cases of gastric carcinoma were identified, including 236 located in the cardia, 341 in the distal part of the stomach (non-cardia), and 336 with overlapping or unknown tumor site. The dietary inflammatory potential was assessed by means of an inflammatory score of the diet (ISD), calculated using 28 dietary components and their corresponding inflammatory scores. The association between the ISD and gastric cancer risk was estimated by hazard ratios (HR) and 95%-confidence intervals (CI) calculated by multivariate Cox regression models adjusted for confounders. Results The inflammatory potential of diet was associated with an increased risk of gastric cancer. The HR (95% CI) for each increase in one standard deviation of the ISD were 1.25 (1.12, 1.39) for all gastric cancers, 1.30 (1.06, 1.59) for cardia cancers, and 1.07 (0.89, 1.28) for non-cardia cancers. The corresponding values for the highest compared to the lowest quartiles of the ISD were 1.66 (1.26, 2.20), 1.94 (1.14, 3.30), and 1.07 (0.70, 1.70) respectively. Conclusions Our results suggest that low-grade chronic inflammation induced by the diet may be associated with gastric cancer risk. This pattern seems to be more consistent for gastric carcinomas located in the cardia than for those located in the distal stomach.